Peacemaking in the New Testament Period - Frizzell, Lawrence E (Journal of Dharma, 1986)
Probably many people in every generation experience events which threaten them or seem to engulf their world in terror. Just as many western historians divide the twentieth century into periods relating to major wars, so it is with biblical history. Key dates are 721 B.C. (the destruction of Samaria and the exile of the ten tribes), 587 B.C. (the destruction of Jerusalem and the Babylonian exile) and 70 A.D. (the second destruction of Jel usalem). All too little attention is given to the principles of peace that undergird the Israelite and Jewish way of life. l A community life that is ordered according to ideals of serving God and loving neighbour (see Deuteronomy 6:5; Leviticus 19:18) should bear some fruit of harmony and tranquility, at least when the circumstances relating to economics and. international politics are favourable. The principles deserve our attention, and even failures in realizing them fully do not invalidate the lessons which may be learned. Considerable space would be required to chart the vicissitudes of the period after the success of the Maccabean revolt in 164 B.C. The Jewish people were favoured with an international situation that permitted growth in relative peace. The author of I Maccabees extolled the rule of Simeon (141-135 B.C.) as a time of peace reminiscent of Solomon’s reign, and described in terms of psalms and prophecies (1 Macc. 14:4-15). Unfortunately, this was short-lived, and on many occasions strife among later Hasmoneans wreaked havoc upon both people and land. On one such occasion in 63 B.C., the Roman legions under Pompey were invited to restore order. The shadow of the Empire over the Near East became less and less benevolent in the minds of the people who eventually found themselves paying heavy taxes and hosting a large military force.